2022
DOI: 10.25259/sni_131_2022
|View full text |Cite
|
Sign up to set email alerts
|

Apoplexy in sellar metastasis from papillary thyroid cancer: A case report and literature review

Abstract: Background: Pituitary metastasis from papillary thyroid cancer (PTC) is rare and only a few cases have been reported. Case Description: We report the case of a patient who presented with visual dysfunction and panhypopituitarism. Magnetic resonance imaging revealed a pituitary tumor and hydrocephalus. Transsphenoidal surgery had been indicated, but his surgery had been postponed due to COVID-19 pandemic. During that waiting period, he showed pituitary apoplexy with consciousness disturbance, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Sixteen studies [ 5 , 9 , 10 , 18 - 20 , 22 - 25 , 29 , 30 , 33 - 36 ] reported other deficient hormones: luteinizing hormone (LH) was the most frequently deficient hormone in 50% (n = 8) of cases while growth hormone deficiency was the least common, occurring in 12.5% (n = 2) of the patients. Serum prolactin was elevated in 63.2% (n = 12) of cases [ 5 , 9 , 10 , 18 , 20 , 21 , 23 , 27 , 30 , 31 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies [ 5 , 9 , 10 , 18 - 20 , 22 - 25 , 29 , 30 , 33 - 36 ] reported other deficient hormones: luteinizing hormone (LH) was the most frequently deficient hormone in 50% (n = 8) of cases while growth hormone deficiency was the least common, occurring in 12.5% (n = 2) of the patients. Serum prolactin was elevated in 63.2% (n = 12) of cases [ 5 , 9 , 10 , 18 , 20 , 21 , 23 , 27 , 30 , 31 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cases without detailed neuro-ophthalmological examinations. Forty-four cases from 38 papers reported the presenting neuro-ophthalmological symptoms, such as visual field defects, vision loss, diplopia, and ophthalmoplegia, were selected [ 1 , 2 , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. The patient information, including age, sex, the time elapsed from primary cancer to the diagnosis of PM, sites of metastasis, treatment, and survival time after diagnosis of PM, were collected ( Supplementary material ).…”
Section: Methodsmentioning
confidence: 99%